The role of national settings in the economic resilience of regions – Evidence from recessionary shocks in Europe from 1990 to 2014 - Christian Hundt; Linus Holtermann (Growth and Change, 2020)
This paper focuses on the particular role of the national setting for the economic resilience of regions during the resistance and recovery phase. Our empirical set-up introduces a spatial hierarchy of 249 NUTS-2 regions nested in 22 European countries while it includes numerous recessionary shocks from 1990 to 2014. Our results suggest that the impact of the national setting is strongest during the resistance phase when the national level accounts for up to 44.9% of the variance in regional GDP development. During recovery, however, the national share decreases but still amounts to no less than 22.0%. Apart from the direct effects that originate from, for example, regulatory density and fiscal policy measures, the national impact takes the form of cross-level moderation effects. These indirect effects indicate that the regional patterns of resilience are additionally shaped by the inter-linkages of country-specific institutional factors and regional determinants. Taking all this into account, regional economic resilience is anything but just a matter of regional capacities.
Keywords: 300